Successful Career Strategy An HR Practitioner's Guide to Reach Your Dream Job - Sommerlatte, Sven. (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2023)
Advancing your career in the best possible way requires a well-structured and targeted approach. This book offers a basic methodology as well as practical tools and a variety of case studies that are helpful for the development and implementation of a career strategy. It helps to match talents with aspirations in order to encourage candidates to make courageous career decisions and offers guidance on how to choose the professional environment that best fits personal preferences. Thus, it can be a guide to considering your career as a lifelong learning journey that can help you grow as a leader and as an individual. The book is primarily aimed at young professionals who want to develop their career in the most effective way. It is also useful for managers to be able to advise and support the professional development of their team members. Videos via app: download the SN More Media app for free, scan a link with play button and access videos directly on your smartphone or tablet.
Chapter 1. Introduction -- Chapter 2. Define Your Career Aspiration -- Chapter 3. Career Strategy - A 5 Step Approach -- Chapter 4. Evaluate Career Opportunities -- Chapter 5. Drive Your Career Development -- Chapter 6. Assess Company Culture -- Chapter 7. Deepen Your Self-awareness -- Chapter 8. Grow as a Leader -- Chapter 9. Make a Great Career Start -- Chapter 10. Conclusion.
Keywords: Personnel management; Personal coaching; Vocational guidance; Industrial organization; Human Resource Development; Coaching; Career Counseling; Organization; Human Resource Management